Taking the next step in digital documentation of historic cities: How hermes evolved in an open data digital library of historic buildings - Chatzigrigoriou, Pavlos (My University, 2016)
When a long-term research finishes, there is always a question about implementation and further development. In the case of HER.M.e.S, the Digital Heritage Management System of the Historic City of Hermoupolis, in a Greek Aegean Island, Syros, it was also a question about raising awareness. The research proved that 2.4 historic buildings collapse every year, as a result of abandonment. This phenomenon was intensified by the severe economic crisis in Greece. The research proposed an optimal conservation plan for the city, after carefully evaluating variables through a multi-criteria model using GIS and an innovating point system. But in order to apply this plan, we need to be able to update the data, as buildings are constantly changing through time. Updating a database with more than 1000 historic buildings, with no funds, is a huge challenge. Soon, we decided that the only way to go is to use a crowdsourcing method. Developing a digital heritage collection portal, using free open source software and serving crucial data for every building, was the answer to our problem. We asked citizens to check the data base, report mistakes, updates, stories, photographs and use the portal to learn about their city. This effort led us to a big digitization project, with up to 1290 historic buildings, 14.400 geo-tagged photos and more than 15.000 fields of information. The project HERMeS, as a conservation plan and a heritage digitization project won the 2015 European Union Europa Nostra Award in Category Research & Digitalisation.
Keywords: Buildings pathology; Conservation; Digital documentation; GIS; Heritage; Historic city; Open data